Molecular Mechanisms Regulating LPS-Induced Inflammation in the Brain - Lykhmus, Olena; Mishra, Nibha; Koval, Lyudmyla; Kalashnyk, Olena; Gergalova, Galyna; Uspenska, Kateryna; Komisarenko, Serghiy; Soreq, Hermona; Skok, Maryna (Frontiers in Molecular Neuroscience, 2016)
Neuro-inflammation, one of the pathogenic causes of neurodegenerative diseases, is regulated through the cholinergic anti-inflammatory pathway via the 7 nicotinic acetylcholine receptor (7 nAChR). We previously showed that either bacterial lipopolysaccharide (LPS) or immunization with the 7(1-208) nAChR fragment decrease 7 nAChRs density in the mouse brain, exacerbating chronic inflammation, beta-amyloid accumulation and episodic memory decline, which mimic the early stages of Alzheimer’s disease. To study the molecular mechanisms underlying the LPS and antibody effects in the brain, we employed an in vivo model of acute LPS-induced inflammation and an in vitro model of cultured glioblastoma U373 cells. Here, we report that LPS challenge decreased the levels of 7 nAChR RNA and protein and of acetylcholinesterase (AChE) RNA and activity in distinct mouse brain regions, sensitized brain mitochondria to the apoptogenic effect of Ca2+ and modified brain microRNA profiles, including the cholinergic-regulatory CholinomiRs-132/212, in favor of anti-inflammatory and pro-apoptotic ones. Adding 7(1-208)-specific antibodies to the LPS challenge prevented elevation of both the anti-inflammatory and pro-apoptotic miRNAs while supporting the resistance of brain mitochondria to Ca2+ and maintaining 7 nAChR/AChE decreases. In U373 cells, 7-specific antibodies and LPS both stimulated interleukin-6 production through the p38/Src-dependent pathway. Our findings demonstrate that acute LPS-induced inflammation induces the cholinergic anti-inflammatory pathway in the brain, that 7 nAChR down-regulation limits this pathway, and that 7-specific antibodies aggravate neuroinflammation by inducing the pro-inflammatory interleukin-6 and dampening anti-inflammatory miRNAs; however, these antibodies may protect brain mitochondria and decrease the levels of pro-apoptotic miRNAs, preventing LPS-induced neurodegeneration.